2011
DOI: 10.1128/iai.00937-10
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid A Phosphate Position Determines Differential Host Toll-Like Receptor 4 Responses to Phylogenetically Related Symbiotic and Pathogenic Bacteria

Abstract: The human symbiont Bacteroides thetaiotaomicron promotes intestinal function and health, whereas the phylogenetically related pathogen Porphyromonas gingivalis is associated with the chronic oral inflammatory disease periodontitis. Although both B. thetaiotaomicron and P. gingivalis synthesize lipopolysaccharides (LPS) consisting of penta-acylated, monophosphorylated lipid A in addition to immunologically silent, nonphosphorylated lipid A, they elicit strikingly distinct Toll-like receptor 4 (TLR4) responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
88
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 29 publications
4
88
0
Order By: Relevance
“…Coats et al (29) suggest that in penta-acyl lipid A species, longer fatty acid chain lengths correlate with greater TLR4 activity. This hypothesis is based on the observation that penta-acyl E. coli LPS with acyl chain lengths of C12 and C14 is a weaker TLR4 agonist in comparison with Porphyromonas gingivalis penta-acyl LPS, which contains acyl chain lengths of C15, C16, and C17 (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coats et al (29) suggest that in penta-acyl lipid A species, longer fatty acid chain lengths correlate with greater TLR4 activity. This hypothesis is based on the observation that penta-acyl E. coli LPS with acyl chain lengths of C12 and C14 is a weaker TLR4 agonist in comparison with Porphyromonas gingivalis penta-acyl LPS, which contains acyl chain lengths of C15, C16, and C17 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Coats et al (29) suggest that in penta-acyl lipid A species, longer fatty acid chain lengths correlate with greater TLR4 activity. This hypothesis is based on the observation that penta-acyl E. coli LPS with acyl chain lengths of C12 and C14 is a weaker TLR4 agonist in comparison with Porphyromonas gingivalis penta-acyl LPS, which contains acyl chain lengths of C15, C16, and C17 (29). In the present study, we have elucidated the genetic reasons for the structural differences between B. pertussis strain BP338 and 18-323 lipid A. lgmA, lgmB, and lgmC are responsible for the GlcN modification present on phosphate groups in BP338, but absent in 18-323, and the single amino acid difference at position 173 of B. pertussis LpxA is responsible for the presence of 14 carbon acyl chains at the C3Ј position in BP338 and only 10 and 12 carbon acyl chains at this position in 18-323.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MPLA works well as a safe and effective vaccine adjuvant. Lipid A structural features known to account for the maintenance of adjuvant properties and the loss of toxicity include the number of phosphate groups, as well as the number, type, and location of fatty acid residues (4)(5)(6). Although the most abundant structure in the S. Minnesota MPLA used in these studies is a hexa-acylated structure (Fig.…”
mentioning
confidence: 99%
“…It is interesting to note that bacteria often evade detection by the immune system via modification of their LPS structures [42][43][44][45]. In fact, the actual position of that single phosphate group on the Lipid A head group affects the potency of host immune responses, with a 4' phosphate being less immune-stimulatory than a l' monophosphate structure [39,46]. This increased potency of a l' versus 4' phosphate may be due to the interaction of the l' phosphate with TLR4, possibly inducing better receptor clustering.…”
Section: Tlr4 Utilizes Both "Tir-domain Containing Adapter Protein Inmentioning
confidence: 99%
“…MPLA represents a structural variant of LPS on commensal bacteria MPLA was first discovered as a hydrolytic derivative of LPS that could be generated in vitro, but recent work has shown that various commensal and opportunistic pathogenic bacteria species produce monophosphorylated LPS, including Bacteroides thetaiotamicron and fragilis, Porphormonys gingivalis, and Heliobacter pylori [38][39][40][41]. It is interesting to note that bacteria often evade detection by the immune system via modification of their LPS structures [42][43][44][45].…”
Section: Tlr4 Utilizes Both "Tir-domain Containing Adapter Protein Inmentioning
confidence: 99%